Arctic and Antarctic. (London : Dorling Kindersley, 2006)
Illustrated photographs and diagrams describe the landscape and wildlife of both the Arctic and Antarctic regions of the earth.
Keywords: Animals -- Polar regions; Natural history -- Polar regions. -- Juvenile literature; Natural history -- Polar regions